YKL‐40 level in gingival crevicular fluid from patients with periodontitis and type 2 diabetes. (6th April 2015) - Kido, J; Bando, Y; Bando, M; Kajiura, Y; Hiroshima, Y; Inagaki, Y; Murata, H; Ikuta, T; Kido, R; Naruishi, K; Funaki, M; Nagata, T
<x xml:space="preserve">Abstract</x> Objective YKL‐40 is a chitin‐binding glycoprotein, the level of which increases in inflammatory diseases, diabetes mellitus (DM), cardiovascular diseases, and tumors. Gingival crevicular fluid (GCF) contains many proteins and markers of periodontitis. The purpose of this study was to investigate YKL‐40 level in GCF from patients with periodontitis and DM and the association between YKL‐40 level and chronic periodontitis (CP) or DM. Subjects and Methods The subjects were 121 patients with DM, CP, DM and periodontitis (DM‐P), and healthy subjects (H). GCF was collected using paper strips after the sites for GCF collection were clinically evaluated for probing depth (PD), gingival index (GI), and bleeding on probing (BOP). YKL‐40 in GCF was identified by Western blotting, and its level was determined by ELISA. Results YKL‐40 was contained in GCF samples from H, DM, CP, and DM‐P sites, and its levels (amount and concentration) in CP and DM‐P were significantly higher than those in H and DM. GCF YKL‐40 level significantly correlated with PD and GI, and its level in BOP‐positive sites was significantly higher than that in BOP‐negative ones. Conclusions GCF YKL‐40 level was elevated in periodontitis, but not DM. YKL‐40 in GCF may be an inflammatory marker for periodontitis.